Differences in the Expression of miRNA-126 and Interleukin (IL)-13 in Fully Controlled and Not Fully Controlled Asthma Patients - Yulia Kartina; Susanthy Djajalaksana; Iin Noor Chozin; Harun Al Rasyid (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Backgrounds: Important finding in the last decades in the field of biology and medicine are micro-RNA (miRNA), including miRNA-126 that are involved in the regulation of interleukin-13 (IL-13) and the T helper 2 cell (Th2) response, the key components of the asthmatic response. The aim of this study is to find the difference in the expression of miRNA-126 and IL-13 serum in fully controlled and not fully controlled groups of stable asthma patients and analyze the relationship between them. Methods: Case-control studies was conducted in 36 stable asthma patients who visited pulmonary outpatient clinic Saiful Anwar Hospital from September 2018 to March 2019. Subjects were divided into 2 groups, each group consisted of 18 fully controlled asthma and 18 not fully controlled asthma patients. The expression of miRNA-126 was measured by the quantitative polymerase chain reaction (q-PCR) and IL-13 using the enzyme-linked immunosorbent assay (ELISA) method. Results: The expression of miRNA-126 was higher in the control group (3.499±2.99) than case group (2.719±2.73), but the difference was not significant (P=0.273). The IL-13 levels were higher in the case group (17.285±9.37) than control group (11.681±5.22), and the difference was significant (P=0.009). However, there was no relationship between the expression of miRNA-126 and IL-13 levels in both groups. Conclusions: There were differences in IL-13 levels, but there were no differences in the expression of miRNA-126 in the two groups. There was no relationship between miRNA-126 expression and IL-13 levels in both groups. (J Respir Indo. 2020; 40(1): 24-32)